What is Contemporary about Institutional Critique?: Or, Instituting the Contemporary: A Study of The Silent University. Issue 6 (1st November 2020) - Tello, Verónica
Abstract: Beginning with a brief analysis of what is broadly considered to be the 'canon' of institutional critique, this article asks: is there anything 'contemporary' about institutional critique? Following the work of Terry Smith and Peter Osborne, by contemporary I mainly refer to the experience of con-tempus, of being with others in time, within increasingly globalised art institutions where the demand of registering disjunctive subject positions – between subjects of the global North and South – is increasingly apparent. While analysing a range of projects, I mainly bring to the fore one work, The Silent University, initiated by Ahmet Ögüt in 2012 and aligned with what has recently been termed the 'fourth wave' of institutional critique, or 'instituent practice'. To my mind, The Silent University offers a productive example of the nexus of contemporaneity, particularly correlative concepts of co-presence and institutional critique. It is an instituent practice founded to contest the individualism of neoliberalism and the divisive effects of globalisation/border politics through explicitly experimental collaborative practices galvanised by the promise of the contemporary 'we'. It is an instituent practice that attempts to forge an infrastructure to sustain radical contemporaneity. In this article, I seek to trace both the potentialities and limitations of the speculative and empirical dimensions of instituent practice, and how it may catalyse the spirit of contemporaneity – being and working together in time against the teleology of global capital – in the context of failing public institutions (the UNHCR, national governments) and the lack of spaces for critical forms of collectivity.